The Impact Of Tourism Village Development On Tourism Business And Community Income Improvement Toward Economic Sustainability - Desman Putra Duha; Haniek Listyorini (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Tourism activities in the village may cause positive and negative impacts for local economy and the sustainability of Tourism destination. This study aims to explain the impact in the development of tourism villages towards of business opportunities, by study on types of business and employment opportunities available in Lerep Tourism Village development, effort to increase community income and economic sustainability from sustainable tourism development in Lerep Tourism Village. The research method used was a qualitative descriptive approach, by conducting in-depth interviews, field observations and document studies that located in Lerep Tourism Village, Semarang Regency. The results of the research obtained, first, there are seven business units business opportunities and employment for local communities. Second, destination Management makes the following efforts in increasing community income: expanding business opportunities, increasing the number of workers, increasing innovation and business licensing, collaborating tour packages, community involvement, and developing tourist attractions. Third, economic sustainability can be realized by involving other supporting aspects, including: Product Aspects, Environment, Socio-Culture, Human Resources, Institutions, Norms, and Pentahelix.